Super-stretchable borophene. (19th December 2016) - Pang, Zhenqian; Qian, Xin; Wei, Yujie; Yang, Ronggui
Abstract: Recent success in the synthesis of the two-dimensional borophene on silver substrates has attracted strong interest in exploring its extraordinary properties for potential technological applications. The single-layer borophene has a buckled structure with atomic ridges. By using the first-principles density functional theory calculations, we show that the two-dimensional borophene is highly stretchable with strong anisotropy The strain-to-failure in the direction along the atomic ridges is nearly twice as large as that across the atomic ridges. The straining-induced flattening and the subsequent stretch of the flat borophene are accounted for the large strain-to-failure for tension along the atomic ridges. We also investigated the mechanics of monolayer borophene under biaxial tension and we found that the biaxial tension increases the strength across the atomic ridges but decreases the failure strain along the atomic ridges. Furthermore, when the bilayer borophene is stretched along the cross-plane direction, the strength and failure strain of the bilalyer borophene are much higher than those of the bilayer graphene due to the very strong inter-layer chemical bonding.